1980
DOI: 10.1152/jappl.1980.48.3.545
|View full text |Cite
|
Sign up to set email alerts
|

Methods for identifying respiratory oscillations disclose altitude effects

Abstract: The respiration of 16 supine subjects was monitored at sea level and at an altitude of 3,050 m. Breath shape was defined by inspiratory and expiratory durations [TI, TE] and volumes [VI, VE], total breath duration [Tt], and ventilation [.VE(=VE/Tt)]. Dynamic breath pattern analysis revealed that the chronological sequences of these variables often display large sustained oscillations. Depending on their relative phase the simultaneous oscillations in VE and Tt are "compensating" or "reinforcing." The first ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
28
0
1

Year Published

1983
1983
2010
2010

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 0 publications
0
28
0
1
Order By: Relevance
“…Brusil and coworkers (8) stated that a breath number time scale is appropriate unless breathing patterns display an extraordinarily large variation in total respiratory cycle time (Ttot). In their study of 16 healthy subjects, the coefficient of variation for Ttot was 20.2 ± 8.6% (mean ± standard deviation) (8). This value is remarkably similar to the value in our 33 subjects (Table I) although our "clamped" data sets show less variability.…”
Section: Experimental Protocolmentioning
confidence: 99%
See 2 more Smart Citations
“…Brusil and coworkers (8) stated that a breath number time scale is appropriate unless breathing patterns display an extraordinarily large variation in total respiratory cycle time (Ttot). In their study of 16 healthy subjects, the coefficient of variation for Ttot was 20.2 ± 8.6% (mean ± standard deviation) (8). This value is remarkably similar to the value in our 33 subjects (Table I) although our "clamped" data sets show less variability.…”
Section: Experimental Protocolmentioning
confidence: 99%
“…This value is remarkably similar to the value in our 33 subjects (Table I) although our "clamped" data sets show less variability. In their series, Brusil and coworkers (8) calculated that over 70% of the observed variability was uncorrelated from breath to breath. We found a similar fraction of uncorrelated variational activity.…”
Section: Experimental Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…Brusil et al (1980) reported that 25 % ofhis sojourners at 3050 m altitude showed 'reinforcing oscillations' during which expired breath volume (VE) and TTOT oscillated out of phase and contributed to increased ventilatory fluctuations. Thus, although hypoxia in the presence of hypocapnic alkalosis may increase variability during wakefulness, it appears that the state of the higher C.N.S.…”
mentioning
confidence: 99%
“…Además, se ha encontrado que la ubicación geográfica, la nutrición y la exposición ambiental influyen sobre la función pulmonar (4,(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21).…”
unclassified